Campbell S. Rapid psychological change / trans. from Engl. O. M. Kadochnikova - O. M. Kadochnikova (Омский научный вестник: Серия "Общество. История. Современность")
The article criticizes the psychological approach to the personal identity problem. An original argument is proposed that emphasizes the difference between gradual and rapid psychological changes. The case of gradual personality changes suggests the presence of psychological continuity in the mental states of a person. It entails that the person survives during such changes. In case of rapid psychological change, the former personality is completely erased by brain-zap to install bit-by-bit a new person at 100 seconds. According to the psychological approach, a person cannot survive during such changes. However, this conclusion leads to a contradiction if we accept Parfit’s principle (which he uses to defend the psychological approach) that what matters in survival cannot depend on a small difference (trivial facts), because such differences are minor